6x2−2xy=3y−11x+2
→2xy+3y=6x2+11x−2
→y(2x+3)=(6x2+9x)+(2x+3)−5
→y(2x+3)=3x(2x+3)+(2x+3)−5
→y=3x+1−52x+3
→5⋮2x+3
→2x+3∈{1,5,−1,−5}
→2x∈{−2,2,−4,−8}
→x∈{−1,1,−2,−4}
→y∈{−7,3,0,−10}
Chúc em học tốt
Ta có :
\(6x^2-2x=3y-11x+2\)
\(\rightarrow2xy+3y=6x^2+11x-2\)
\(\rightarrow y\left(2x+3\right)=\left(6x^2+9x\right)+\left(2x+3\right)-5\)
\(\rightarrow y\left(2x+3\right)=3x\left(2x+3\right)+\left(2x+3\right)-5\)
\(\rightarrow y=3x+1-\dfrac{5}{2x+3}\)
\(\rightarrow5⋮2x+3\)
\(\rightarrow2x+3\in\left\{1,5,-1,-5\right\}\)
\(\rightarrow x\in\left\{-1;1;-2;-4\right\}\)
\(\rightarrow y\in\left\{-7,3,0,-10\right\}\)